Strength analysis of reinforced concrete flexural members at not entirely use of reinforcement resistance (Academic journal Industrial Machine Building Civil Engineering, 2019)
The suggestions for the engineering calculation of the reinforced concrete flexural members strength during the elastic workof steel are given. The engineering technique is developed on the basis of a nonlinear deformation model application usingfractionally rational function for describing the process of concrete compressed area deformation and other prerequisites thatare recommended by current norms for the reinforced concrete structures design. The analytical dependences have been obtainedfor determining the neutral axis depth and the calculation of the internal bending moment value perceived by the beamin the normal section. The task of determining the load-bearing capacity of the bending element is reduced to searching bythe direct analytical dependences the maximum value of the bending moment that can be perceived by the beam at givenstrains of the most compressed rib of a cross-section.
Keywords: reinforced concrete; beam; strength; analysis